GAMBARAN HEMOGLOBIN DAN NEUTROFIL PASIEN KEMOTERAPI KANKER PAYUDARA DI ONKOLOGI CENTER RSUD Dr. SOETOMO SURABAYA: HEMOGLOBIN AND NEUTROPHIL OF BREAST CANCER CHEMOTHERAPYPATIENTS AT THE ONCOLOGY CENTER OF Dr. SOETOMO HOSPITAL, SURABAYA - Rachmaningtyas, Arie; Sundari, Titik; Rini, Yenny Puspa; Wijayanti, Christina Destri Wiwis (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2024)
Breast cancer management is chemotherapy. One of the negative impacts of chemotherapy is affecting hemoglobin and neutrophils. This study aims to determine the description of Hemoglobin levels and Neutrophil counts in breast cancer patients undergoing chemotherapy stage 1 (early) and stage 6 (late) at the Oncology Center of Dr. Soetomo Hospital, Surabaya. This study is an observational study with a retrospective design. The sample in this study was some breast cancer patients undergoing chemotherapy stage 1 (early) and 6 (late) at the Oncology Center of Dr. Soetomo Hospital, Surabaya, which was taken as many as 25 people by purposive sampling. Purposive sampling. The study was conducted in the Oncology Center laboratory of Dr. Soetomo Hospital, Surabaya. This study was conducted from October to December 2022. The results of the study showed that breast cancer patients undergoing stage 1 chemotherapy mostly had normal hemoglobin as many as 13 people (52%) with an average Hb level of ± 12.34 g / dL and normal neutrophils as many as 23 people (92%) with an average neutrophil level of ± 4412 cells / µL. In stage 6 chemotherapy, most had low hemoglobin as many as 13 people (52%) with an average Hb level of ± 11.78 g / dL and normal neutrophils as many as 24 people (96%) with an average number of neutrophils of 4202.68 cells / µL.